2007
DOI: 10.1098/rstb.2007.2219
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of substrate water interactions at the high-affinity Mn site in the photosystem II oxygen-evolving complex

Abstract: 18O isotope exchange measurements of photosystem II (PSII ) in thylakoids from wild-type and mutant Synechocystis have been performed to investigate binding of substrate water to the highaffinity Mn 4 site in the oxygen-evolving complex (OEC). The mutants investigated were D1-D170H, a mutation of a direct ligand to the Mn 4 ion, and D1-D61N, a mutation in the second coordination sphere. The substrate water 18 O exchange rates for D61N were found to be 0.16G0.02 s K1 and 3.03G0.32 s K1 for the slow and fast pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
0
29
0
2
Order By: Relevance
“…The D1-D61N mutation slows down both W s and W f exchange rates by 3 and 6.5 times, respectively [20]. This is especially surprising because mutations of some of the direct ligands to the OEC, such as D1-D170 and D1-E189, have less …”
Section: Water Substrate Exchangementioning
confidence: 97%
“…The D1-D61N mutation slows down both W s and W f exchange rates by 3 and 6.5 times, respectively [20]. This is especially surprising because mutations of some of the direct ligands to the OEC, such as D1-D170 and D1-E189, have less …”
Section: Water Substrate Exchangementioning
confidence: 97%
“…Additionally, the residues D1-D61 and CP43-R357, which have been proposed to be important in the deprotonation steps during the S-cycle (Dau and Haumann 2008;Knoepfle et al 1999;McEvoy and Brudvig 2004;McEvoy et al 2005;Sproviero et al 2006Sproviero et al , 2008a form parts of these channels. More recently, these residues have also been shown by mutagenesis studies to be very important to optimal S-cycling and O 2 evolution, even without being ligands to the CaMn 4 cluster (Debus 2005;Hwang et al 2007;Singh et al 2008 channels, the assignment of the large channel system for O 2 exit was preferred, as its volume and numerous exits may facilitate rapid removal of O 2 compared to the much narrower back channel. Also, it was found by comparison with cryogenic electron microscopy of PSII supercomplexes that the large channel system would direct O 2 away from the associated chlorophyll-rich subunits and light harvesting complexes.…”
Section: Studies Of Channels In Psii By Computer Modelling Since the mentioning
confidence: 99%
“…This work has indicated that H-bonding is critical in the binding process (Noguchi andSugiura 2000, 2002b). Interestingly water exchange measurements conducted in the S state of a D1:D170H mutant show no significant difference in the rates of exchange of either fast or slow exchanging water sites between the mutant and wild-type PSII (Singh et al 2008). Surprisingly, this indicates that D170 mostly likely does not ligate a Mn that binds a substrate water molecule as D170 is thought to ligate the dangler Mn4 and is widely considered to be a substrate water binding site.…”
Section: Substrate Binding-locationmentioning
confidence: 95%